THE ROLE OF AI, IOT, AND RFID-BASED DIGITAL INVENTORY CONTROL SYSTEMS IN IMPROVING OPERATIONAL AND FINANCIAL PERFORMANCE (A STUDY OF RETAIL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2020-2024) - Jeje Huraeji; Hadiah Fitriyah (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to determine the role of AI, IoT, and RFID-based digital inventory control systems in improving the operational and financial performance of the retail industry in Indonesia. Operational performance is measured by inventory turnover, while financial performance is measured by gross profit margin, net profit margin, and return on assets. Method: This study uses secondary data, namely data provided by retail companies listed on the Indonesia Stock Exchange during 2020-2024. The sample was selected using a purposive technique of 22 companies. The method used was simple linear regression analysis. Results: The results of this study show that, first, there is no effect of the digital inventory control system variable on inventory turnover. Second, there is an effect of the digital inventory control system variable on gross profit margin. Third, there is an effect of the digital inventory control system variable on net profit margin. Fourth, there is an effect of the digital inventory control system variable on return on assets. Fifth, there is an effect of the digital inventory control system variable on financial performance. Novelty: The novelty of this study lies in examining the role of AI, IoT, and RFID-based digital inventory control systems specifically on both operational performance—measured by inventory turnover—and multiple dimensions of financial performance, including gross profit margin, net profit margin, and return on assets, using retail companies listed on the Indonesia Stock Exchange during 2020-2024. This research provides a new perspective by integrating advanced digital technologies into the analysis of performance indicators in the Indonesian retail industry.